Islamic Education Policy in the New Order Era - Hidayah, Nurul; Arifin, Syamsul; Humaidi, Nurul (Belajea: Jurnal Pendidikan Islam, 2024)
Islamic education existed before the founding of the Indonesian state. Many Muslims participated in fighting for Indonesian independence. For this reason, Islamic education and the Indonesian state have a very close relationship, including the New Order era, which was the forerunner to the progress of Islamic teaching. This research aims to determine Islamic Education policies during the New Order era and the supporting factors for improving Islamic Religious Education. The research method used is a literature review by collecting various sources of books, articles, and documents about Islamic education policies during the New Order era. The results of the research obtained are that the New Order era opened the door to the entry of Islamic Education into national education with the SKB of three Ministers, the renewal of madrasas and Islamic boarding schools, the empowerment of non-formal Islamic Education Institutions, and the improvement of the socio-religious atmosphere in the community, as well as various factors. Other supporters who led to the progress of Islamic education during the New Order era.